Design of Speed Interface for 20 MVA Metallurgy Rolling Drive System - HUANG Jiade; LUO Yunfei; GUO Zan; WU Bin (Kongzhi Yu Xinxi Jishu)
Based on the control requirements of 20 MVA metallurgy rolling drive system on motors, it designed the hardware and the software structure of a speed interface system with incremental encoder and absolute encoder. The circuit principle, FPGA internal function and the software flow were mainly analyzed. This design greatly improves some performances of the speed interface system in the application of the drive control system, such as the compatibility, anti-interference and efficiency of data collection.